PENERAPAN MESIN IRAT BAMBU DAN DIGITALISASI PENJUALAN PRODUK UNTUK SENTRA ANYAMAN BAMBU DI DESA BANJARWARU - Rahmat, Saepul; Purnata, Hendi; Diantono Abda'u, Prih (Universitas PGRI Yogyakarta, 2025)
Usaha Karya Bamboo Weaving Center is a bamboo weaving craft institution located in RT 02 RW 04 Dusun Bokol Kulon, Banjarwaru Village. It is managed independently by Hadi Tuslam Ranantika together with the community. This group started the business with 14 members who were tasked with making bamboo weaving crafts based on local wisdom, such as bags, clothes, baskets, bamboo boxes, flower vases, tissue holders, and other accessories. The biggest problem partners face is that the large number of orders cannot be fulfilled due to the limited availability of raw bamboo weaving materials. This is because they still rely on the conventional bamboo weaving process, which is labor-intensive and requires limited human resources to prepare the weaving materials. The purpose of this activity is to address the poor management system, which causes low efficiency in operations, quality control, and hinders long-term planning. Community service activities, including the application of bamboo weaving machine technology and the creation of a product sales system website for the bamboo weaving center in Banjarwaru Village, have helped increase the productivity and sales of partner products. The production results from the shredding machine enable the preparation of material requirements for 60 products per day, thereby exceeding the demand for raw materials by 50 products per day. Keyword: Solar PV; Bamboo Slicing Machine; Renewable Energy